Zur politischen Relevanz raumbezogener Diskurse.: Das Beispiel der Naturschutzpolitik in der Europäischen Union - Chilla, Tobias (ERDKUNDE, 2007)
Within human geography, the perception has by now taken hold that space is not only restricted to its material dimension, but that the processes of its social and discursive construction need to be taken into consideration as well. This article aims to contribute to the current debate on the social construction of space, based on an empirical analysis of the formulation and implementation process of the EU Habitats Directive, which aims to protect fauna, flora and habitats within the multi-level system of the European Union: First, drawing on empirical findings, the article identifies the constructions of space in different phases of the political process of the Habitats Directive and discusses their political purposes. In doing so, the close connection of the discourse on space to representations of nature and Europe becomes obvious. Second, the article argues that not only the construction of space serves political purposes but also the denial of space. De-territorialisation or even de-spatialisation can be seen as political tools as well. Third, the article cautions with regard to the popular slogan space matters, to understand discursive constructions of space as automatically carrying political power. The insights of institutional theory might offer a perspective for more differentiating approaches.